ENHANCEMENT OF OPTICAL NONLINEARITY IN A QUEST HOST SYSTEM BY NEMATIC ORDERING - PARK, B; EOM, SY; LEE, SD; CHOI, DH; PARK, SY; KIM, N (CHAPMAN HALL LTD, 1995)
Second-harmonic generation (SHG) has been studied for understanding the enhancement mechanism for the second-order optical nonlinearity by the nematic (or axial) ordering in a liquid crystal doped with one-dimensional nonlinear optical (NLO) organic molecules. An extended version of the Maier-Saupe mean-field theory for nematic liquid crystals was developed to obtain analytical expressions for the second-order NLO coefficients in terms of the axial order, the polar order and the effective nematic potential. From the SHG data in a guest-host system composed of N,N'-dimethylaminonitrostilbene molecules (0.5% by weight) and a liquid crystal, the enhancement of the second-order NLO coefficient, d33, by nematic ordering becomes almost 3, which agrees well with our theoretical predictions.
Keywords: POLED POLYMER-FILMS; 2ND-HARMONIC GENERATION